The Barbagli technique: 3‐year experience with a modified approach. (18th September 2012) - Pfalzgraf, Daniel; Kluth, Luis; Isbarn, Hendrik; Reiss, Philip; Riechardt, Silke; Fisch, Margit; Dahlem, Roland
Abstract : What's known on the subject? and What does the study add? Urethral strictures can be treated by various methods, e.g. dilatation and endoscopic treatment, as well as with open surgery. However, transurethral treatment shows low long‐time success rates, while open urethral reconstruction yields good long‐term results. One of the standard procedures to reconstruct the strictured penile urethra is the Barbagli technique, which was introduced in 1996. However, a potential drawback of this technique is the suturing of the urethral margins to the second side of the graft, because the buccal mucosa is already fixed to the corpus cavernosum and the last line is sutured in the back side of the urethra out of sight. The present study aims to assess whether the functional results are compromised by a modified Barbagli technique, which enables a better visualisation of the mucosal margins while making the anastomosis, simplifying the original technique. OBJECTIVE: To evaluate stricture recurrence rate as well as the satisfaction with the surgery of patients treated with a modified Barbagli technique published by our study group in 2009. PATIENTS AND METHODS: Retrospective analysis by patient's chart review and unvalidated standardised questionnaire of patients treated by the modified Barbagli technique for urethral stricture between May 2008 and September 2010. In all, 22 patients were treated with the modified Barbagli technique for urethral stricture during this time, and 18 patients were available for follow‐up. Previous surgeries, recurrence rate, complications, incontinence, erectile function, satisfaction with the surgery, and oral numbness were assessed. As described in the original technique, also in the modified technique the access to the urethra is achieved through a midline incision. Subsequently, the urethra is completely mobilised. However, it is then rotated 180 ° using stay sutures. Afterwards, the buccal mucosa is sutured into the opened urethra on both sides under vision, giving free access to the margins. Once the buccal mucosa is completely sutured in, the urethra is back‐rotated using stay sutures and the margin of the buccal mucosa and the urethra is sutured to the tunica albuginea, stretching and supporting the buccal mucosa. RESULTS: Follow‐up was available for 18 patients with a mean (range) age of 67.5 (27–74) years. Open previous surgeries had been performed in 27.8% and transurethral surgeries in 72.2%. The mean (range) length of the oral mucosa graft was 7.8 (2.5–13) cm and the mean operative duration was 106 (73–193) min. The success rate was 83.2%; there was no de novo erectile dysfunction and no relevant penile curvature. There was oral numbness in two patients (9%). None of the recurrence‐free patients (83.3%) were dissatisfied with the surgery. CONCLUSIONS: The technique simplifies the original technique without compromising the functional results. The modification of the technique enables a better visualisation of the mucosal margins while making the anastomosis, simplifying the original technique. The success rate was comparable with the original technique and patient satisfaction with the surgery was high.